2013
DOI: 10.1007/978-3-642-38323-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Trust within Online Discussion Boards: Trust Formation in the Absence of Reputation Systems

Abstract: Abstract. Trust plays an important role when it comes to sharing and picking up information on the Internet. Even more so when advice is being exchanged and decisions are being made based on what at first sight seems to be interpersonal communication between people who do not know each other. Research concerned with the role of trust in making an assessment of online user-generated information, often focuses on online reputation systems rather than on the way individuals try to evaluate peer recommendations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…He makes a distinction between people who are somewhat knowledgeable themselves -who can test the person both formally and informally -and people who are not knowledgeable -and who will have to rely on reputation or performance. Previous research also indicated reputation and performance as key elements for trust [4].…”
Section: Cognitive Authoritymentioning
confidence: 94%
See 3 more Smart Citations
“…He makes a distinction between people who are somewhat knowledgeable themselves -who can test the person both formally and informally -and people who are not knowledgeable -and who will have to rely on reputation or performance. Previous research also indicated reputation and performance as key elements for trust [4].…”
Section: Cognitive Authoritymentioning
confidence: 94%
“…100% experience without any study or some kind of WTCB 4 hassle" In a next example, instead of using the experience of a construction professional to boost a message, the authority of the construction professional is being questioned. In the first fragment (figure 2 -different discussion) a member rejects the advice of a construction contractor as a suitable source of information within the specific context of soil stability.…”
Section: "[A] Below You Find a Table With Indications On Moss Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…In a virtual research environment it may be the case that both types of interpersonal trust exist simultaneously for different users. Reputation, knowledge communities, institutional affiliation and past experience may be utilised to establish competence, commitment, and credibility and hence trust in other people [21,33,56,112,116]. However, this can be challenging online, particularly if a stakeholder does not have any experiential knowledge or prior interactions with others in the community.…”
Section: Trust In Peoplementioning
confidence: 99%